A multilevel selection model for prosocial well-being - Larsen, Mads; Witoszek, Nina; Yeung, June Chun (Frontiers in Psychology, 2023)
This article proposes an evolutionary model for well-being informed by multilevel selection. We posit that people’s subjective assessment of their own quality of life is the sum their happiness, which is related to individual selection, and their sense of having a meaningful life, which is related to group selection. Conceptualizing life quality as “Happiness + Meaning = Well-being” offers insights into how the human well-being system helps people navigate between individual and group needs. We define happiness as the cluster of affects that reward individuals for solving adaptively relevant problems. We approach meaning as a reward individuals experience when contributing to their community. While people derive happiness from cooperation and competition, meaning originates from prosocial (cooperative/altruistic) behavior. Since increased within-group competition often reduces societal well-being, public policy should aim at cooperative means for good living. Our model brings attention to these dynamics. The Nordic countries, which score highest on quality of life, facilitate multilevel well-being, that is, individual prosperity and altruistic opportunity. Our preliminary quantitative study confirmed the correlation between some markers of prosociality and well-being at a national level. To investigate the psychological mechanisms behind this correlation, we conducted in-depth interviews of Nordic and Slavonic helpers of Ukrainian refugees in Norway (n = 32). A primary ambition was to illuminate how the human quest for meaning contributes both to individual flourishing and group selection. In line with Nesse’s view on happiness not as an affect meant to be maximized, but an evolutionary signal, we use a qualitative approach that allows for a deeper understanding of how individuals adapt to these signals. Our findings suggest that happiness is transient so that the well-being system’s signal sensitivity can be preserved. Meaning is enduring since it assesses and reinforces social belonging. These insights are relevant for our era’s turn toward more holistic development policies. Compared to often materialistic, competition-driven happiness pursuits, meaning-driven well-being is a more sustainable alternative for individuals, communities, and the planet.